2019
DOI: 10.19044/esj.2019.v15n19p129
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Self-Confidence Restoration with Peer Mentoring Strategy

Abstract: The research objective is to restore students' self-confidence in learning process using peer mentoring strategies. The research design used is classroom action research by involving students who experience selfconfidence problems determined purposively (five participants). Data were collected using participant observation, in-depth interviews, and field notes. Data were analyzed quantitatively (frequence and percentage) and qualitatively using Creswell's model with seven segments of analysis, ranging from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The existence of student awareness will be able to increase students' self-confidence so that in doing everything related to productive competency material students are confident that they will be able to do it well (E. MacQuillan, 2018;Ray et al, 2021). Other research found that productive competence has a positive and significant effect on self-efficacy (Blegur et al, 2019;Nurlaela et al, 2020). Apart from that, research similar to this research was also conducted who stated that competency in productive accounting training courses had an effect on the self-efficacy of class XII students in the accounting skills program by 3.5% (Nurhayati & Kusmuriyanto, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of student awareness will be able to increase students' self-confidence so that in doing everything related to productive competency material students are confident that they will be able to do it well (E. MacQuillan, 2018;Ray et al, 2021). Other research found that productive competence has a positive and significant effect on self-efficacy (Blegur et al, 2019;Nurlaela et al, 2020). Apart from that, research similar to this research was also conducted who stated that competency in productive accounting training courses had an effect on the self-efficacy of class XII students in the accounting skills program by 3.5% (Nurhayati & Kusmuriyanto, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This enables students to show appreciation, which is a form of peer emotional support that encourages selfimprovement. The nuance of appreciation also applies to persons that have unsuccessfully tried to build their confidence, and ensures that students remain involved in group discussion in order to complete their assignments (Blegur, Wasak, & Rosari, 2019). Furthermore, students' need to start appreciation with simple statements such as, "Wow!…”
Section: Appreciation From Peers Strengthens Group Learning Commitmentsmentioning
confidence: 99%